THE EFFECT OF UNIVERSITY ENTRANCE SELECTION PATHWAY ON FIRST-YEAR GPA OF UNDANA MATHEMATICS EDUCATION STUDENTS - Christine Krisnandari Ekowati; Siprianus Suban Garak; Patrisius Afrisno Udil; Imelda Hendriani Eku Rimo (Academic Journal of Educational Sciences, 2021)
This study aims to see whether the university entrance selection path significantly affects the first-year GPA of UNDANA Mathematics Education students. This research was carried out in the mathematics education study program FKIP UNDANA by taking data on the university entrance selection path of 220 mathematics education students who entered in 2014 – 2020 and their GPA data after studying for one year in the mathematics education study program. This data then analyses using simple linear regression theory – one categorical independent variable with several categories assisted by the SPSS application. The study results show that the university entrance path has a significant effect on the first-year GPA of mathematics education students. The F value obtained is 5.043 with sig. = 0.007 < 0.05, so the hypothesis H0 is rejected, and Ha is accepted. In addition, this study also shows that students with SNMPTN entrance pathways have a higher average first-year GPA than students with SBMPTN and SMMU entry pathways.